Persistent Müllerian ducts syndrome A case report - Yasseen, Hadeel A; Hama, Mahdi A; Faisal, Ghasak Ghazi (Seventh Sense Research Group, 2019)
Persistent mullerian duct syndrome (PMDS) is usually an accidental finding during routine inguinal hernia repair in male patients. Intraoperatively, mullerian remnants consisting of an infantile uterus and fallopian tubes are usually found. Herein we report a case of PMDS in a 3-year-old boy presenting with unilateral undescended testes.The right testis was not palpable and the diagnostic ultrasound shows a non-visualized right testis neither in scrotum nor in the right inguinal region.